The tree of enlightenment : an introduction to the major traditions of Buddhism - Della Santina, Peter; Singapore Buddhist Meditation Centre (Singapore : Singapore Buddhist Mediation Centre, 1997)
Transcript of lectures by the author.
Keywords: Buddhism -- Doctrines; Buddhist philosophy